Hadith Tracking Traveling Women Without Mahram - Desma Wahyuni; Rozian Karnedi (Journal of Indonesian Islamic Studies, 2023)
The purpose of this article is to mentakhrij hadith about the prohibition of women to travel without mahram by the method of "takhrij bi al-lafdz", or takhrij based on the first pronunciation of the hadith. The conclusion of this article is the first, women are prohibited from traveling without a muhrim with him if traveling a day / night or three days or more in hajj, or ordinary travel that is not maintained security and safety for the woman. Second, the permissible departure of women is if it meets the conditions, among others: with the permission of the husband, covering the awrah, the atmosphere of safe travel, not tabarruj even though the time taken does not reach a day overnight. Third, the hadith concerning the prohibition of women traveling without mahram includes hadith ahad mashhur. Therefore, it can be used as hujjah with the exception of the situation of a safe country, and maintained the safety of muslim women while traveling. The statement based on the opinion of the scholars who concluded that the requirement of mahram participation is not an absolute requirement, but rather a necessary requirement on the way out of the city that is not guaranteed security, both from crime and from other slanders.